Impact of thermal focal shift on laser cutting processes with high brightness lasers - Eiselen, Sasia; Zapf, Heiko; Mantel, Eugenia; Hofmann, Lukas-Matthäus; Schmidt, Michael (2012)
The increasing use of high brightness lasers with power in the kilowatt range for laser fusion cutting processes leads to advantages concerning yield and quality. Conversely these laser sources are very susceptible to external disruptions and therefore tend towards instable processing This becomes noticeable in the thermal focal shift which is influenced by many different factors during the process and can easily extend the Rayleigh length. The authors report on investigations of influences on the thermal focal shift using different optical configurations in laser cutting with single mode and multi mode high power fiber lasers. Changes of the beam caustic could be observed due to the optical components in the laser processing head including the fiber end block. In consequence of the measured drift of up to multiples of the Rayleigh length the focal shift has a high impact on the cutting results. Investigations about the impact of this drift on fusion cutting processes for metal sheets with thicknesses of 0.1 mm to 1.5 mm were conducted and a feasible technique for experimental determination of thermal instabilities such as the laser induced focal shift could be demonstrated.